Analyzing factors of Gui simulation as learning media toward students' learning outcomes - I Gusti Putu Asto Buditjahjanto (OmniaScience, 2022)
The use of simulation tools has been widely used to learn something. Simulation tools have the advantage of imitating a process similar to the actual situation. But there are only a few researches that examine the students' engagement in using simulation tools in the learning process so that it affects the student learning outcomes. This research aims to analyze the factors of GUI simulation as learning media for learning signal coding technique based. PLS-SEM method was used to investigate the impact and the relationship of factors of GUI simulation such as easiness of use, media attractiveness and learning content toward learning outcome. The results showed that the learning content factor gave a large and significant contribution toward learning outcomes, while easiness of use and media attractiveness made a small contribution to the learning outcome.